Influence of stoichiometry on the performance of MIM capacitors from plasma‐assisted ALD SrxTiyOz films. Issue 2 (9th September 2013) - Aslam, N.; Longo, V.; Keuning, W.; Roozeboom, F.; Kessels, W. M. M.; Waser, R.; Hoffmann‐Eifert, S.
<x xml:space="preserve">Abstract</x> Strontium titanate, SrxTiyOz (STO), thin films with various cation stoichiometries were deposited by plasma‐assisted atomic layer deposition (ALD) using cyclopentadienyl‐based metal precursors and oxygen plasma as counter‐reactant. [Sr]/([Sr] + [Ti]) compositions ranging from 0.46 to 0.57 were obtained by changing the (SrO)/(TiO2) ALD cycle ratios. As‐deposited 15–30 nm thick SrxTiyOz films prepared at 350 °C on Pt‐coated silicon substrates were amorphous. Post‐annealing at 600/650 °C for 10 min under N2 gas resulted in a crystallization into the perovskite phase. Stoichiometric STO and Sr‐rich STO films exhibited a certain degree of (111) texture while the Ti‐rich STO films showed a lower degree of crystallization. Crystallized layers exhibited a smaller band gap Eg than amorphous ones, while within the stoichiometry series the value of Eg increased with increasing Sr‐content. Within the stoichiometry series Pt/STO/Pt structures with Sr‐rich STO films showed the lowest leakage current densities. At 1.0 V values of about 2 × 10−8 and 5 × 10−6 A cm−2 were obtained for the as‐deposited and the annealed films, respectively. Highest capacitance density was obtained for 15 nm polycrystalline stoichiometric SrTiO3 films resulting in a capacitor equivalent thickness CET of about 0.7 nm. Pt/SrxTiyOz/Pt capacitors with the STO being in amorphous state exhibited a positive voltage nonlinearity factor α of about 400 ppm V−2, while the negative α‐values for crystallized films showed a systematic variation with the stoichiometry, the degree of crystallization and the thickness of the STO layer. This demonstrates that a broad performance range of MIM capacitors is accessible by controlling the stoichiometry and the degree of crystallization of plasma‐assisted ALD SrxTiyOz thin films.